(untitled) (De la Crítica, 2025)
This monographic work aims to analyze the constructs of cohesion and coherence in written language to establish conceptual clarifications that facilitate the distinction between both, report some of their applications, and suggest their implications in the fields of didactics and research. Initially, cohesion will be analyzed as a linguistic-textual property that materializes the relationship between language and discourse (Halliday and Hasan, 1976). Subsequently, coherence will be addressed as a product that emerges thanks to the psycholinguistic skills of the reader, which can be induced but not guaranteed by cohesion (Hatch, 1992; Martínez, 2001). As the exposition unfolds, results from studies in which these constructs have served as a basis for investigating the production and/or processing of different discourse genres will be reported.